Impact of NPK and micronutrients fertilization on beans in Nicaragua - Siles, Pablo; Tellez, Orlando; Peng, Yuan-Ching; Zeledón, Yasser; Urroz, Norman (International Center for Tropical Agriculture, 2020)
This dataset contains information of experiments carried out beans in two regions of Nicaragua (Northern of the Central Region and Southern of the Pacific Region), as well as a compilation of soils data from different regions in Nicaragua collected from 2015 to 2019. The experiments were designed to explore the effects of macronutrients (N, P, K) and micronutrients (Zn + B + Mg) in the yield of beans. The experiments were carried out in the farmer's field during the 2019 production cycle (Apante sowing), the dataset contains yield and aerial biomass of the experiments.